Analisis Biaya Produksi dan Analisis Profitabilitas Usaha Budidaya Ikan Lele di Kab. Mojokerto - Firdaus, Adam Sabili; Nugroho, Prasetyo (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
This study aims to analyze production costs in catfish curl farming in Mojokerto Regency and compare the level of profitability. The research sample is several respondents of catfish farming farmers in Mojokerto district. This study used primary data and secondary data obtained from catfish farmers, relevant agencies, the Mojokerto District Fisheries Office, and the Ministry of Maritime Affairs Fisheries, using purposive sampling method. The data analysis technique used in this research is quantitative descriptive analysis. The final results of the study showed that farmer-2 was superior in obtaining a lower FCR value of 1.16 compared to farmer-1's FCR level of 1.60. However, the profit gain and the level of profitability obtained are much greater in the enlargement of catfish owned by farmer-1 with a profitability rate of 16.90%. This occurs because the costs incurred to purchase feed in the form of CCM waste are far more expensive than the costs incurred to purchase feed in the form of chicken intestines. In terms of feed quality, CCM waste is of good quality and efficient for use as catfish feed because it can score low FCR values. However, the costs incurred to purchase good quality feed also need to be taken into account and considered.